(untitled) (Международный научный журнал «Инженер», 2026)
This article presents a statistical analysis of the volume of freight turnover in automobile transport for the period 2010–2023. The analysis was performed using Minitab 17 software, with linear and quadratic trend models constructed and their accuracies compared. Additionally, the autocorrelation of model residuals was examined, and a forecast of freight turnover volume for 2024–2026 was made. The results indicate an increasing annual growth trend in freight volume. These results are of great importance for the development of transport infrastructure, the improvement of logistics systems, and the identification of investment directions. During the analysis, the time dynamics of the variables were thoroughly studied, and statistically grounded conclusions were drawn. The findings enabled the formulation of practical recommendations that can be applied in economic forecasting.